[(2³)⁴:(2⁵)²+(5³)⁷:(5⁴)⁵]:3-3=
Răspunsuri la întrebare
Răspuns de
7
Răspuns:
Explicație pas cu pas:
[ ( 2^3)^4 : (2^5)^2 + (5^3)^7 :(5^4)^5 ] : 3 - 3 =
(2^3×4 : 2^5×2 + 5^3×7+ 5^4×5 ) :3-3 =
(2^12 : 2^10 + 5^21 : 5^20 ) :3-3 =
(2^12-10 + 5^21-20) : 3 - 3 =
(2^2 + 5^1 ) : 3 - 3 =
(4 + 5 ) : 3 - 3 =
9 : 3 - 3 =
3 - 3 =
0
romannarcisadrian123:
Multumesc mult
Răspuns de
2
Explicație pas cu pas:
( 2^3×4:2^5×2+5^3×7:5^4×5):3minus 3=
(2^12:2^10+5^21:5^20):3minus 3=
(2^2+5^1):3minus 3=
(4+5):3minus 3=
9:3minus 3 =
3minus 3=
0
R:0
Alte întrebări interesante
Istorie,
8 ani în urmă
Matematică,
8 ani în urmă
Biologie,
8 ani în urmă
Fizică,
9 ani în urmă
Biologie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă